PENGEMBANGAN VIDEO PEMBELAJARAN KINEMASTER BERBASIS LITERASI SAINS DI SEKOLAH DASAR - Agustia Tri Andani Agustia; Aan Subhan Pamungkas; Ana Nurhasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
This study aims to determine the process of development, feasibility, and student responses to kinemaster learning videos based on scientific literacy in class V SDN Karundang 2 Serang. This study uses a 4D development model consisting of four stages, namely define, design, develop, and disseminate. Data collection techniques used are in the form of interviews, observations, questionnaires, and documentation. The instruments used were interview sheets, observation sheets, validation questionnaire sheets, and student response questionnaire sheets. The results of the research on developing kinemaster learning videos based on scientific literacy obtained an average score of 87.14% from media experts with very decent criteria, material experts 91.76% with very decent criteria, and linguists 82.5% with very good criteria. worthy. The results of the student response questionnaire obtained from small group trials get a score percentage of 87.5% and large group trials get a score percentage of 86.64% including very good criteria. Thus, from the results of this study, it can be concluded that the kinemaster learning video based on scientific literacy for elementary school students was successfully developed, suitable for use in the learning process, and received a good response from students by using this learning video in learning.